Breastfeeding by Working Mothers: Global Challenges - Yvan Vandenplas; Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
A mother’s full-time employment is a determinant factor in abandoning exclusive breastfeeding before 6 months. White-collar workers have a better knowledge, attitude, and practice toward breastfeeding than blue-collar workers. The discontinuation of exclusive breastfeeding is associated with delayed skin-to-skin contact, Neonatal Intensive Care Unit admission, pacifier and artificial teats use, mother’s return to work earlier and lower education levels. Racial and ethnic disparities in paid and unpaid workloads of mothers, and the relationship between components of job quality and duration of mother’s own milk provision. However, returning to work, insufficient breast milk, misconceptions about breastfeeding, and interference with social life were the barriers for mothers to breastfeed continuously. Several aspects must be considered to increase the chances of a beneficial effect of interventions: type of intervention, target audience, timing of intervention, actors that can implement it, strategies and methods of intervention, and intensity of intervention. Intervention efforts should focus on behavior change to educate and equip mothers to overcome the barriers that are within their control. Such interventions should further focus on family-centered education and strengthening the proficiency of healthcare workers on advising breastfeeding mothers. Findings point to the importance of health visitors providing emotional support to bolster the continuation of breastfeeding and encourage a positive subjective experience of infant feeding. The emphasis of emotional support encourages increased allocation of resources and training opportunities to ensure health visitors are able to provide enhanced emotional support. Women’s experiences reveal a daily life with difficulties in reconciling the desire to breastfeed and the work scenario. Support network and adaptation to children’s food routine are strategies adopted to minimize risks of weaning. The results show the need to consolidate policies to encourage continued breastfeeding in the labor market. Effort is needed to sustain breastfeeding after maternal return to work. A breastfeeding-friendly policy with clear operating guidelines in the workplace is critical to sustaining breastfeeding. Learning from others who have had a positive experience will ensure that all breastfeeding women are better supported in the workplace in future. When ‘breastfeeding only’ support is offered to women, the duration and in particular, the exclusivity of breastfeeding is likely to be increased. Support may also be more effective in reducing the number of women stopping breastfeeding at three to four months compared to later time points. For ‘breastfeeding plus’ interventions the evidence is less certain. Support may be offered either by professional or lay/peer supporters, or a combination of both. Support can also be offered face-to-face, via telephone or digital technologies, or a combination and may be more effective when delivered on a schedule of four to eight visits. Further work is needed to identify components of the effective interventions and to deliver interventions on a larger scale. Governments should make it obligatory for employers to offer a breastfeeding support program and a dedicated breastfeeding facility at the workplace as these simple measures significantly increase exclusive breastfeeding. Knowledge improvement related to breastfeeding benefits and supports to working mothers are a key priority, however advocacy to employers, managers, and supervisors in providing breastfeeding facilitation and program support are also critical to successful breastfeeding practice among workers. Policies, regulations, and laws supporting the promotion of exclusive breastfeeding practices until 6 months in mothers as recommended by the WHO should be reinforced.